Estimation of age in forensic anthropology: historical perspective and recent methodological advances - Douglas H. Ubelaker; Haley Khosrowshahi (Oxford University Press, 2019)
Estimation of age represents a central focus of forensic anthropological analysis of human skeletal remains and of the living. Advances registered in recent research include the topics of taphonomic impact, new anatomical areas of interest, histology, population variation, the dental pulp chamber, technology, mathematical approaches, biochemical analysis and techniques specifically targeting the living. This article reviews the historical development of age estimation methods and considers likely future directions.